Relative Coagulation Potentials of Aluminum Sulphate and Mangifera indica Seeds in Purifying Domestic Waste Water - Adeniran, K. A.; Dunmoye, I. D. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
The high cost of most chemical coagulants and their non-availability coupled with their negative health impacts necessitates the use of natural or bio-coagulants. This study compares the effectiveness of using powdered extract from matured dried Mangifera indica (M. indica) seeds (bio-coagulant) with Aluminum sulphate (alum, chemical coagulant) for the coagulation of domestic waste water. The treatments include: control culture (no coagulant is added), 150 mg/L of alum, 100 mg/L, 150 mg/L and 200 mg/L of M. indica seeds. All the treatments were cultured in 15-litres buckets. The experiment was design based on Completely Randomized Design (CRD) replicated 3times. Physical, chemical and bacteriological properties of the domestic sewage were determined before and after the application of the coagulants on weekly basis. Results show that for turbidity, at the point of collection, the value was 013NTU was reduced to a minimum value of 001NTU for both 100 mg/L and 150 mg/L of M. indica seeds treatments. The Total Hardness at the point of collection was 2.73 mg/L; the highest value during the period of study was 5.30 mg/L at the fifth week for the alum treatment, followed by 4.37 at the fourth week for 100 mg/L of M. indica seeds treatment. The study showed that M. indica seeds powder perform very well as a bio-coagulant and be used as a replacement for alum or any other chemical coagulant in the purification of domestic waste water.Kathmandu University Journal of Science, Engineering and TechnologyVol. 13, No. 2, 2017, page:26-38